Analysis of Methanol Content in Different Varieties of Traditionally Fermented Alcohol Found in Chandannath Municipality of Jumla District, Nepal - Acharya, Apurba; Kaphle, Sushma; Aryal, Bijay; Shakya, Arbin (Journal of Karnali Academy of Health Sciences, 2023)
Background: Alcohol poisoning associated with traditionally fermented alcoholic beverages have been reported in Nepal with the constituents of these beverages not being quantified usually. In traditionally fermented alcoholic beverages, methanol, due to its cheaper cost and similar physiochemical properties with ethanol, is adulterated most commonly and readily. Methods: The present study is a cross-sectional study in which four different types of traditionally fermented alcoholic beverages were collected from Chandannath, Jumla and they were analyzed for methanol content. From Chandannath municipality, the ward number two was selected for collection of samples. Further, from this ward, four different households regularly involved in brewing local alcohol were also randomly selected. These households belonged to three different ethnic groups (Indo-Aryan, Tibeto-Burman and Newar) and these samples were chhyang (sample- 1), local raksi (sample- 2), nigar (sample- 3) and local apple cider (sample- 4). In air tight containers, the samples were sealed and transported to Zest laboratory, Bhaktapur, Nepal for quantification of methanol using Gas Chromatography.Results: The residents in half of these four households belonged to the Tibeto-Burman ethnic groups. Methanol was detected in two samples among the four analyzed beverages. These samples, sample- 2 and sample- 4, on quantification showed the concentrations of 10.050ppm and 13.721ppm of methanol respectively.Conclusion: Among four samples of locally brewed alcoholic beverages, methanol was detected in two samples, but at a concentration below the level that would be considered toxic.